2022
DOI: 10.22201/fe.01851667p.2022.322.82471
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Economic Complexity: A Multisectorial Empirical Analysis

Abstract: This paper aims to analyze empirically how manufacturing, disaggregated into subsectors by research and development (R&D) intensity, influences the level of economic complexity (eci). For this, two methods were used: 1) the parametric by Panel Dynamic Ordinary Least Squares (pdols) and 2) the non-parametric: a) Data Envelopment Analysis (dea) and b) Malmquist Decomposition. The econometric results suggest that the allocation of workers in the manufacture of high R&D level has a positive impact on the eci level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…This result is typical since, through learning by doing and specialization, both skilled and unskilled labor of this sector experience growth in productivity and acquire the know-how needed to produce sophisticated goods. This result corroborates those of Nepomuceno Lima et al (2022), who showed that employment in high R&D sectors of manufacturing is positively associated with EC in both developed and developing countries. Indeed, according to Rodrik (2013), manufacturing is the only sector with characteristics consistent with unconditional convergence.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This result is typical since, through learning by doing and specialization, both skilled and unskilled labor of this sector experience growth in productivity and acquire the know-how needed to produce sophisticated goods. This result corroborates those of Nepomuceno Lima et al (2022), who showed that employment in high R&D sectors of manufacturing is positively associated with EC in both developed and developing countries. Indeed, according to Rodrik (2013), manufacturing is the only sector with characteristics consistent with unconditional convergence.…”
Section: Resultssupporting
confidence: 91%
“…A positive and robust relationship is reported between industrialization as proxied by MVA and EC. According to Nepomuceno Lima et al (2022), industrialization is an essential driver of EC due to its ability to perform research and development, implement new technologies, and spur the production of complex products. Natural resource rents have a negative and significant effect on EC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations